Bahasa Inggris - Sonki Prasetya; Cecep Slamet Abadi; Cherly Zahara Siregar; Tatun Hayatun Nufus (Recent in Engineering Science and Technology, 2023)
Mekartani Farm is a comunity located at Jl. Mataram III RW 06, Kelurahan Mekar Jaya, Kecamatan Sukmajaya, Depok City, West Java Mekartani Farm is managed by Mr. Ferryzar. The implementation of PLTS aims to reduce the electricity costs that are still charged to local residents due to planting activities. The study analyzed solar irradiation data as well as data on total electricity loads and daily energy needs at the Mekartani Farm. The PLTS system designed at the Mekartani Farm is capable of generating 1347.7 kWh of energy in a year and has batteries with a capacity of 100 Ah, three of which are arranged in parallel to provide a backup for two days of autonomy. Using a 400 WP solar panel of two parallel-set units with an efficiency of 20.57%.